Significance of preventing radicalism among students through strengthening religiousness and Pancasila ideology in Indonesia - Yani, Muhammad Turhan; Ahmadi, Anas; Hazin, Mufarrihul; Akmal, Muhammad Hakim; Nasih, Ahmad Munjin (Edelweiss Applied Science and Technology, 2025)
Student radicalism poses a severe danger to the nation’s social stability and ideology. This study aims to examine the effect of Islamic Religious Education (PAI) lecturers in universities in East Java in preventing radicalization by improving moderate religious understanding and comprehension of Pancasila ideology. The study used in-depth interviews and surveys of PAI lecturers from several state and private universities to collect the data. The results indicated that strengthening an inclusive and moderate understanding of religion and instilling Pancasila values was effective in protecting students from the influence of radical ideology. PAI lecturers also played a role in supervising religious activities on campus, ensuring that these activities remained within the corridor of moderation and tolerance. This study emphasized the importance of synergy between strengthening moderate religious education and socializing Pancasila values to form strong ideological resilience among students. This study also conveyed the need for support from educational institutions and the government in maintaining an inclusive campus environment free from radicalism.